Penerapan Strategi Learning Start with a Question Dalam Meningkatkan Hasil Belajar PAI di SMP IT Nurul Ilmi - Izzati, Aufi Nadra; Rustam, Rustam (Jayapangus Press, 2025)
This study aims to describe the effectiveness of the implementation of the Learning Starts with a Question strategy in improving the learning outcomes of Islamic Religious Education (PAI) at SMP IT Nurul Ilmi. The background of this research is the low active participation of students and the understanding of the material that is not optimal. This strategy was chosen because it emphasizes questions as a starting point for learning, which has the potential to encourage critical and active student engagement. This study uses a qualitative approach with a case study method. The research subjects consisted of one PAI teacher and three grade VIII students at Nurul Ilmi IT Junior High School. Data was collected through observation, in-depth interviews, and documentation, which were then analyzed with stages of reduction, presentation, and conclusion drawn. The results of the study show that the Learning Start with a Question strategy is effective in improving student learning outcomes, both cognitively and affectively. Cognitively, this strategy has been proven to facilitate a deeper understanding of the material, which is reflected in the average grade point average that reaches above the KKM. Affectively, this strategy successfully fosters active participation, courage to ask questions, and a positive attitude towards learning. Teachers act as facilitators who manage discussions, while students become more independent and motivated. However, there are challenges related to students' readiness to read the material and the lack of parental support. Overall, this study concludes that the Learning Starts with a Question strategy is an effective method to create interactive, participatory, and holistic PAI learning.